2008
DOI: 10.1016/j.jvs.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary responses to treadmill and cycle ergometry exercise in patients with peripheral vascular disease

Abstract: These results demonstrate that exercise testing using cycling offers an alternative method of cardiopulmonary testing for patients with IC that is equally reliable and reproducible to treadmill walking. Cycling may be preferable to treadmill exercise because it induces greater cardiopulmonary and metabolic responses and is better tolerated by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
16
1
1
Order By: Relevance
“…Generally, healthy controls have ICCs in the range of 0.85 to 0.98 for VO 2 peak and maximal heart rate (4,20,21). Turner et al (22) reported high correlations for peak heart rate (r=0.94) and peak oxygen uptake (r=0.98) in subjects with peripheral arterial disease and claudication. Riebe (16) also reported high intraclass correlations for peak oxygen consumption (r = 0.97) in patients with peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, healthy controls have ICCs in the range of 0.85 to 0.98 for VO 2 peak and maximal heart rate (4,20,21). Turner et al (22) reported high correlations for peak heart rate (r=0.94) and peak oxygen uptake (r=0.98) in subjects with peripheral arterial disease and claudication. Riebe (16) also reported high intraclass correlations for peak oxygen consumption (r = 0.97) in patients with peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 99%
“…There has been the suggestion to evaluate PAD patients using a cycle ergometer to avoid the gait problems during treadmill walking. However, the outcome of limited performance and pain onset was similar to that achieved during walking, although a higher cardiopulmonary response could be elicited (940). Treatment of PAD patients with pentoxifylline or cilostazol, which improves exercise tolerance, does not improve gait abnormalities (429, 430).…”
Section: Training Improves Walking Efficiency In Pad Patients Durimentioning
confidence: 93%
“…A number of studies have demonstrated leg ergometry to be an effective approach for improving walking and/or cycling outcomes for PAD patients [3437]. Additionally, Tuner et al [38] evaluated absolute claudication time and cardiorespiratory outcomes during incremental cycling and treadmill exercise testing in a group of PAD patients with IC. Results indicated similar absolute claudication time outcomes between the two modalities in addition to significantly higher cardiovascular and metabolic responses during leg ergometry compared to treadmill walking.…”
Section: Exercise Therapy For Claudicationmentioning
confidence: 99%
“…able to induce IC thus providing specific training to affected lower limbs in addition to central cardiovascular adaptations [38]…”
Section: Tablementioning
confidence: 99%